Current Concepts on Gastric Carcinoid Tumors - George C. Nikou; Theodoros P. Angelopoulos (Gastroenterology Research and Practice)
Gastric carcinoid tumors (GCs) are rare lesions representing less than 10% of carcinoid tumors and less than 1% of all stomach neoplasms. There are three distinct types of gastric carcinoids; type I includes the vast majority (70–85%) of these neoplasms that are closely linked to chronic atrophic gastritis. Type II which accounts for 5–10 %, is associated with Zollinger-Ellison syndrome and often occurs in the context of multiple endocrine neoplasia type 1. Type III, finally, represents 15–25% of gastric carcinoids and is characterized by a far more aggressive course. The optimal clinical approach to GCs remains to be elucidated, depending upon type, size, and number of carcinoids. While there is universal agreement about the surgical treatment of type III GCs, current options for type I and II include simple surveillance, endoscopic polypectomy, surgical excision associated with or without surgical antrectomy, or total gastrectomy. Moreover, the introduction of somatostatin analogues could represent another therapeutic option.